Development of a Prototype Renewable Energy System and its Modification to Suit Middle East Applications - Salman K Salman (Iraqi Journal for Electrical and Electronic Engineering, 2011)
This paper concerns with exploitation of renewable energy sources for meeting energy requirements of remote locations. It presents an investigation which is based on a practical project that was executed in collaboration between academia and industry. It involves design and installation of a prototype integrated renewable energy system which consists of two 15 kW wind turbines, electrolyser, fuel cell system (FCS) and the associated control equipment. It was installed at the furthest island of Shetland, North of Scotland, U.K. The philosophy used in designing this system is summarised as follows: During times of high wind, the electricity generated by wind turbines is normally greater than that required by site electrical load. The excessive amount of generated electricity is stored into Hydrogen by utilising an electrolyser which is then used to generate the deficient electric power by the FCS at times of low wind.